Population Dynamics of Major Insect Pests on Ailanthus excelsa Roxb. And their Management in Arid and Semi-Arid Areas of Rajasthan and Gujarat - Sharma, Meeta; Sharma, Noopur; Srivastava, K. K.; Parmar, Ashok (Indian Forester, 2016)
In the past few years, problems of land degradation and unavailability of intensive agricultural system to farmers have encouraged them to grow more multipurpose trees species such as Ailanthus excelsa. It is an important agro-forestry tree species. The demand for Ailanthus excelsa has increased for its valuable use as fodder, firewood, medicine, timber, toy making, packing and plywood, matchstick industries etc. It can be easily grown in adverse conditions of desert regions of Rajasthan and Gujarat being a salt tolerant species. An extensive surveywas made in Tonk area of Rajasthan and Mehsana of Gujarat. It was found that A. excelsa is affected by a number of insect pests infesting the whole lot of plantation and farmlands. A total of thirty-one species of insect and non-insect pests have been recorded to cause minor to severe levels of damage to the root, shoot, bark, leaf, seed, flower and fruits of A. excelsa plantations. Therefore, the present study aims at measuring the damage intensity caused by major pests and thereby finding control measures to bring their population to non-destructive minimal levels.